The effect of corporate governance and risk taking on financial performance of Malaysian banks - Nodeh, Fazel Mohammadi (2016)
Corporate governance in both financial and non-financial firms is an important issue by researchers. A large number of corporate scandals across the world are due to financial scandals, weaknesses and failures in corporate governance, as well as risk taking that could attribute to poor financial performance. This study focused on the effects of corporate governance characteristics (board independence, board size, independent risk management committee, risk management committee size, independent audit committee, audit committee size and ownership concentration) on financial performance and risk taking. The study also assessed the role of risk taking as mediator on relationship among corporate governance and financial performance, besides comparing the financial performance of Islamic and conventional banks. This study was based on data collected from 37 published annual reports of Malaysian banks (21 conventional and 16 Islamic banks) for the period between 2005 to 2014. Data were analyzed using ordinary least square, fixed effect, generalized method of moments, approach of Baron and Kenny, Sobel test and independent t-test. The results stated that financial performance is positively related to corporate governance characteristics and there is a significant relationship between corporate governance and risk taking. On the other hand, risk taking plays the role of mediator between four characteristics of corporate governance (board independence, independent risk management committee, independent audit committee and ownership concentration) and financial performance in all banks as well as conventional banking sectors. Result of the study also showed full mediation between board independence and financial performance while partial mediation between independent risk management committee, independent audit committee and ownership concentration with banks financial performance. In contrast, risk taking has not mediated the relationship between board size, risk management committee size and audit committee size with financial performance in all banks, conventional and Islamic banks. However, there were significant differences between the financial performance of Islamic and conventional banks. This study contributes to the continuing debate on corporate governance and financial performance by providing a timely investigation of banks corporate governance, financial performance and risk taking. This study highlights the importance of effective future public policy to understand which aspects of corporate governance have the greatest impact on financial performance after considering risk taking.